(untitled) (Research, Society and Development, 2022)
Chemistry is a science that needs contextualization to arouse students’ interest and promote meaningful learning. In addition, this science has an important role in our diet, as it is present in nutrients, vitamins, fats, etc., so it is essential to study the properties of the food we eat daily. Thus, this work aims to encourage the teaching of chemistry through contextualization, aiming at the study of food chemistry as a generative theme for the subject of acids and bases, and to make students aware of changing eating habits. The research was developed in a 9th grade class of elementary school at a public school located in Nova Floresta-PB, through two theoretical and practical classes and the application of a questionnaire. Given the results obtained, the importance of relating chemistry to the daily lives of students was perceived, as this generates a broader view of the theory in the students and helps them find solutions in everyday situations. It was also noticed the importance and need for more practical classes. The intervention was satisfactory and the proposals were successfully achieved, it being clear that the students understood the importance and concepts of the study of acids and bases with the food approach.